Star trek: the next generation: intelligence gathering ebook Intelligence gathering. - Tipton, David (Star Trek: The Next Generation: Intelligence Gathering (2008)., 2014)
IDW's Star Trek comics line launched with Star Trek: The Next Generation - The Space Between, a series of six stand-alone issues. Now, prepare for the latest voyage of the Enterprise as the creative team that brought you Klingons: Blood Will Tell tackles an all-new Star Trek: TNG mini-series. Author: Scott Tipton, David Tipton. Illustrator: David Messina. © 2014 Paramount Pictures Corporation. © CBS Studios Inc.